The Effect of Perceived Parent–Child Facial Resemblance on Parents’ Trait Anxiety: The Moderating Effect of Parents’ Gender - Yu, Quanlei; Zhang, Qiuying; Chen, Jianwen; Jin, Shenghua; Qiao, Yuanyuan; Cai, Weiting (Frontiers in Psychology, 2016)
Father-child facial resemblance is an important cue for men to evaluate paternity. Previous studies found that fathers’ perceptions of low facial resemblance with offspring lead to low confidence of paternity. Fathers’ uncertainty of paternity could cause psychological stress and anxiety, which, after a long time, may further turn into trait anxiety. Conversely, females can ensure a biological connection with offspring because of internal fertilization. The purpose of this study was thus to examine the role of parents’ gender in the effect of parents’ perceived facial resemblance with child on their trait anxiety. In this study, one hundred and fifty-one parents (father or mother) from one-child families reported their facial resemblance with child and their trait anxiety. Results showed that (a) males tended to perceive higher facial similarity with child than did females, and (b) males’ perceived facial resemblance with child significantly predicted trait anxiety, whereas females’ perceived facial resemblance did not. These findings suggested that the uncertainty of paternity contributed to the trait anxiety of fathers, but not mothers.